2021
DOI: 10.1177/15589447211028918
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of COVID-19 on Hand Trauma

Abstract: Background The Coronavirus Disease 2019 (COVID-19) pandemic has had a dramatic impact on individual and societal behaviors, as well as on health care systems. It confers a unique opportunity to examine the relationship among disease, policies, and patterns of activity, as well as their impacts on surgical unit functionality. This study aims to compare the distribution and patterns of injury at a tertiary hand surgery trauma center before and during the COVID-19 pandemic. Methods A retrospective analysis of all… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 11 publications
1
15
0
Order By: Relevance
“…Westmead Hospital in Sydney, Australia, reported a 40% to 52% decrease in road trauma in 2020 when compared to the preceding period ( 15 ). The institution in the current study recorded similar trends in general orthopaedic and hand trauma from motor vehicle accidents in the same period ( 6 , 7 ). The increased proportion of cycling-related trauma is likely multifactorial, with the Sydney City Council reporting a monthly increase in rates of cycling traffic up to 50% in certain areas of Greater Sydney in April 2020, despite a reduction in overall people movement of 87% ( 16 ).…”
Section: Discussionsupporting
confidence: 64%
See 1 more Smart Citation
“…Westmead Hospital in Sydney, Australia, reported a 40% to 52% decrease in road trauma in 2020 when compared to the preceding period ( 15 ). The institution in the current study recorded similar trends in general orthopaedic and hand trauma from motor vehicle accidents in the same period ( 6 , 7 ). The increased proportion of cycling-related trauma is likely multifactorial, with the Sydney City Council reporting a monthly increase in rates of cycling traffic up to 50% in certain areas of Greater Sydney in April 2020, despite a reduction in overall people movement of 87% ( 16 ).…”
Section: Discussionsupporting
confidence: 64%
“…This study showed that neither time to theatre nor mean surgical time was significantly increased between the two cohorts [consistent with the prior literature]; however, time inside the operating theatre was significantly increased, which is most likely due to time required to implement the risk reduction strategies for aerosolising procedures ( 17 , 18 ). Interestingly, these findings are not consistent with operative intervention in general orthopaedic and hand trauma from the same institute, with total surgical time decreasing in both respective pandemic cohorts ( 6 , 7 ).…”
Section: Discussionmentioning
confidence: 77%
“…The authors did not use telemedicine, and Toia et al [11] as well as Leti Acciaro et al [27] confirmed it might be an issue in Italy. To reduce contamination risks [28], some surgeons increased non-surgical treatment [9,23], and to resolve issues linked to a diminution of anesthetists' availability, many hand surgeons [9,12,14,17,24,29] stated to use WALANT surgery [30].…”
Section: Discussionmentioning
confidence: 99%
“…The COVID-19 pandemic and related policies have also shed impact on the frequency and disease distribution of emergency department visit because of the geographic restriction and changes in daily activities (4). As for hand trauma, although the incidence of emergency visit decreased globally in the first wave of the pandemic, the rate of emergency operation was reported unchanged and eventually the incidence returned to normal and remained unaffected by the following pandemic waves (5)(6)(7)(8).…”
Section: Introductionmentioning
confidence: 99%
“…Replantation of severed digits represents a hallmark in hand surgery, and survival rate of the digits has been increasing thanks to advances in microsurgery (9). Meanwhile, the rate of emergency digit replantation was reported to be relatively constant and even higher during waves of pandemic (4,5,10).…”
Section: Introductionmentioning
confidence: 99%